Effectiveness of Probing-prompting Learning Models with Scaffolding Strategy to Mathematic Creative Thinking Ability and Enthusiasm - Alfian, Miftah Hafidz; Dwijanto, Dwijanto; Sunarmi, Sunarmi (Unnes Journal of Mathematics Education, 2017)
The purpose of this research was to know that the learning model ProbingPrompting with Scaffolding strategy effective on the mathematic creative thinking ability and enthusiasm. Based on the research results in students population in class VII SMP N 1 Adiwerna in the academic year 2016/2017, used techunique random sampling there are class VII A as experimental class and class VII B as control class. The research total show that in experimental class is reached out classical. The difference test of two average mathematic creative thinking abilities indicates that students' mathematic creative thinking ability in the experimental class is better than the control class. The difference test of two average of enthusiasm shows that enthusiasm students in the experimental class is better than the control class. The conclusion of this research is ProbingPrompting learning model with scaffolding strategy effective to the mathematic creative thinking ability and enthusiasm.